Reincarnating Shakespeare’s sister: Virginia Woolf and the “uncircumscribed spirit” of fiction - Naomi TOTH (E-REA)
In order to explore the relationship between the fictional, the spiritual, and the feminine in Virginia Woolf’s thought, two of her important essay-manifestos, “Modern Fiction” (1919/1925) and A Room of One’s Own (1928), are read here in parallel. In “Modern Fiction”, Woolf describes the task of writers as that of capturing an “unknown, uncircumscribed spirit”, otherwise defined as “reality”, “truth” or “life itself”. This “spirit” or vital “reality”, however, is constituted in the movement of the writing subject towards it, a movement that dissolves the boundaries between subject and object. It is also represented as immanent to the material world, capable of investing the subject in a “moment of vision”. The tension established between the writing subject and this vital “spirit” or “reality” has implications for the relationship between women and fiction Woolf imagines in A Room of One’s Own. For the movement of the writing subject beyond the self and towards the vital “spirit” of the “real” proves to be essential for the reincarnation of “Shakespeare’s sister”, that is, for the creation of a genuinely feminine literature.